High‐Fidelity Dimerization of Xanthenyl Radicals and Dynamic Qualities of a Congested Ethane: Diethyl Dixanthenyl‐9, 9′‐Dicarboxylate. Issue 1 (20th December 2021) - Hogan, David T.; Dubrawski, Zachary; Gelfand, Benjamin S.; Sutherland, Todd C.
Abstract: Exploration of the sterically‐congested ethane diethyl dixanthenyl‐9, 9′‐dicarboxylate has revealed the dynamic behavior arising from its congested C−C bond. Interlocking 'geared' substituents and favorable dispersion interactions around this bond result in a conformational preference for partially cofacial xanthene moieties both in solid state and as dilute solutions. The weak, centrally located C−C bond is 1.628 Å long and permits selective thermolysis to yield two carbon‐centered ethyl xanthenyl‐9‐carboxylate radicals, which dimerize with high fidelity into the original sterically‐congested ethane. Recombination of the radicals into this symmetrical head‐to‐head dimer is highly reproducible – by observing the equilibrium, the bond dissociation enthalpy was calculated to be 20.4 kcal ⋅ mol −1 . The substituents around the central carbon provide insufficient stabilization against oxygen, which consumes the radicals and unbalances the dimer‐radical equilibrium. Abstract : Thermolysis of the central weak C−C bond in a symmetrical xanthenyl dimer produces two carbon‐centered xanthenyl radicals. Dissociation is highly reversible – the radicals couple exclusively in a head‐to‐head fashion that reforms the original sterically congested ethane, which itself exhibits restricted rotation about the central ethane C−C bond.